A differential study about beliefs of persons infected by the human immunodeficiency virus (HIV), related to the psychological coping with the conditions of the contagion - Figueiredo, Marco Antonio de Castro; Terenzi, Natalia Maria; Machado, Alcyone Artioli (Medicina (Ribeirao Preto), 1999)
Study Model: these results indicate some distinctive characteristics among subjects in terms of self-responsibility and beliefs of a necessary reason about problems related to aids. Considering these differences, some characteristics are discussed which may guide future subsidiary orientation strategies for the clinical treatment of aids.: a differential study. Objective: the impact of Acquired Immunodeficiency Syndrome (aids) on the affective integrity of carriers and symptomatic patients exacerbates patient feelings of insecurity and of loss of control over the situation during which care is provided. This fact reflects on patient response to treatment, with a negative influence on his compliance with prescribed procedures: thus, previous knowledge about the way the patient evaluates the causes of the disease and his own resources to cope with it represents a reference framework of great importance for the conception of care strategies. In this respect, the present study was designed in order to determine the different forms of psychological coping with HIV contagion by persons with aids. Methodology: the present investigation consisted of two studies: A) 30 patients with HIV, symptomatic or not, ranging in age from 19 to 59 years were evaluated by the Control Locus Scale of Levenson which permitted their classification into three categories: internal (whose control is attributed to the person itself), external (whose control is exerted by stronger others or by the context), and teleologic (whose control emanates from a superior power or divine will). B) In a second study, 40 symptomatic patients seen at public and private clinics were evaluated by an adaptation of the Levenson scale contextualized for aids. Results: differential subgroups were identified (p>.05). In the first study there was a prevalence of externality responses conjugated with teleology among women (.59+,17>+.08; p<.001); in the second there was less propensity to teleology among users of private services compared to users of public services (-.32<+.12; p<.001), as well as a greater internality among the latter (+.44>+.26; p=.02). Conclusions